The GO License : Only Part of the Solution - Batson, A.; Milstien, J. B. (2012)
The Generic Open (GO) License is a proposal to make patents more accessible for vaccines and drugs in low- and middle-income countries. However, for some health-related products, such as vaccines, intellectual property is frequently not the primary constraint. Technical know-how and assurance of a viable market built on reliable demand at prices that cover costs are the most critical factors for vaccine access. Together with innovative efforts to reduce product development risks and costs and to assure credible markets at profitable prices, the GO License may yet play a role in assuring access for drugs and vaccines for poor countries.